2018
DOI: 10.1371/journal.pone.0196006
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory dysfunction as a prognostic marker for disability progression in Multiple Sclerosis: An olfactory event related potential study

Abstract: Multiple sclerosis (MS) is a chronic inflammatory disease and one of the leading causes of disability in young adults. Functional markers able to predict MS progression are still lacking. It is recognized that olfactory dysfunction may be an early symptom in MS. The aim of this study was to investigate whether alterations in olfactory event-related potentials could play a prognostic role in MS. Thirty patients affected by MS relapsing-remitting underwent an olfactory potential examination (T0). Three years aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 20 publications
0
9
3
Order By: Relevance
“…Previous research found that olfactory dysfunction might be associated with current EDSS, 6,9 although this effect seemed to be mild 9 ; however, the olfactory event-related potential method was used, and the time of prospective observation of patients was longer (3 years) than that in our research (12 months). 6 Previous studies concerning cognition and olfaction produced contradictory results. 8,9 One large study including 146 patients with MS found that mean olfactory bulb volume did not correlate with neuropsychological testing, 8 which was similar to the results of our study.…”
Section: Discussioncontrasting
confidence: 58%
“…Previous research found that olfactory dysfunction might be associated with current EDSS, 6,9 although this effect seemed to be mild 9 ; however, the olfactory event-related potential method was used, and the time of prospective observation of patients was longer (3 years) than that in our research (12 months). 6 Previous studies concerning cognition and olfaction produced contradictory results. 8,9 One large study including 146 patients with MS found that mean olfactory bulb volume did not correlate with neuropsychological testing, 8 which was similar to the results of our study.…”
Section: Discussioncontrasting
confidence: 58%
“…Recent studies have established anosmia as a prodromal biomarker for Alzheimer's disease (48)(49)(50) and the presence of olfactory deficits in a subset of MS patients correlating with symptom severity (51,52). GAS-infected mice show severe persistent physiological deficits in M/ T neuronal function (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of demyelinating plaques observed by MRI in the inferior frontal-and temporal-lobe regions of patients affected from MS is correlated with altered smell abilities and olfactory dysfunctions. As in case of gustatory alterations, the olfactory dysfunction may be an indicator of disease progression due to the increasing of number of lesion or to the extension of demyelinating areas 32,33 .…”
Section: Smell Alterations In Msmentioning
confidence: 99%